NEW PRESUMPTION PROCEDURE: GROSS PROFIT MARGIN WEIGHTED AVERAGE - Alarcón Vargas, Freddy (2015)
As is known, one of the Tax Administration (SUNAT) faculties is the determination of the tax liability on presumptive basis.We propose a new presumption procedure based on the analysis of documents and information of the ins-pected companies. In such way, we would be respecting the principles of contributory capacity and economic reality of taxpayers.This procedure complements what is stated in paragra-ph 1 of Article 93 of the Law of Income Tax, which es-tablishes the “Presumption of sales or revenues adding to the sales cost of what is declared or registered by the tax debtor, the result of applying to that cost the gross profit margin weighted average of similar companies. In many years of my work as a tax auditor, I have seen that when this presumption is applied, generally the amounts determined as omitted revenues are very high amounts, getting away from the economic reality of enterprises without respecting their capability to pay.